2011
DOI: 10.3415/vcot-10-11-0156
|View full text |Cite
|
Sign up to set email alerts
|

Use of an axial pattern skin flap based on the cranial cutaneous branch of the saphenous artery in the dog

Abstract: An axial pattern skin flap based on the cranial cutaneous branch of the saphenous artery is a viable option for closing medial crus skin defects in the dog.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 9 publications
(17 reference statements)
1
7
0
Order By: Relevance
“…Degner et al noted two cutaneous branches, the more proximal of which coursed caudally and proximally, with the more distal branch extending cranioproximally . This latter branch was identified by Collins and others as the CCSA and was reliably identified in all dogs of our study. Kostolich and Pavletic described the genicular branch originating just proximal to the bifurcation of the saphenous artery into cranial and caudal branches at the level of the proximal medial tibia, noting that paired branches were sometimes present.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Degner et al noted two cutaneous branches, the more proximal of which coursed caudally and proximally, with the more distal branch extending cranioproximally . This latter branch was identified by Collins and others as the CCSA and was reliably identified in all dogs of our study. Kostolich and Pavletic described the genicular branch originating just proximal to the bifurcation of the saphenous artery into cranial and caudal branches at the level of the proximal medial tibia, noting that paired branches were sometimes present.…”
Section: Discussionsupporting
confidence: 73%
“…The value, reliability, and robustness of perfusion studies as a tool to predict clinical outcomes requires further investigation. The single case report of the CCSA axial pattern flap that inspired this investigation involved elevation of a smaller flap than our study has suggested might be viable from the observed angiosomal boundaries. It cannot be inferred that the data presented here accurately reflect what might be clinically applicable.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The cranial cutaneous saphenous flap has only been reported in a single case (Collins et al . ) and is best suited to defects of the medial aspect of the stifle. The genicular artery arises as single or paired vessels arising from the saphenous artery where it passes over the medial surface of the stifle.…”
Section: Introductionmentioning
confidence: 99%
“…Axial pattern flaps based on the superficial caudal epigastric (Aper & Smeak 2005, Bauer et al 2005, Pavletic 1980), cranial cutaneous saphenous (Collins et al 2013) and genicular (Kostolich 1987) arteries have application to skin deficits of the pelvic limb distal to the stifle. Depending on the conformation of the dog, it may be difficult for the caudal superficial epigastric flap to reach very far distal to the stifle (Pavletic 1980).…”
Section: Introductionmentioning
confidence: 99%